Laboratory Testing for the Evaluation of Phenotypic Activated Protein C Resistance - Morimont, Laure; Donis, Nathalie; Bouvy, Céline; Mullier, François; Dogné, Jean-Michel; Douxfils, Jonathan (Seminars in Thrombosis and Hemostasis, 2022)
Activated protein C (APC) resistance (APCR) is considered a risk factor of venous thromboembolism (VTE). The most common genetic disorder conferring APCR is a factor (F) V Leiden mutation, but many other factors are also implicated, such as other F5 mutations (e.g., FV Hong-Kong and FV Cambridge), protein S deficiency, elevated factor VIII, exogenous hormone use, pregnancy and postpartum, depending on how APCR is defined. Considering the large population affected, the detection of this phenotype is crucial. Two types of tests are currently available: clotting time-based assays (with several versions) and thrombin generation-based assays with the endogenous thrombin potential (ETP)-based assay. The purpose of this review is therefore to discuss the performances of these tests and the cases in which it would be appropriate to use one over the other. Initially, as APCR was thought to be solely related to the FV Leiden mutation, the objective was to obtain a 100% specific assay. Clotting-time based assays were thus specifically designed to detect this inherited condition. Later on, an APCR condition without a FV Leiden mutation was identified and highlighted as an independent risk factor of VTE. Therefore, the development of a less specific assay was needed and a global coagulation test was proposed, known as the ETP-based APCR assay. In light of the above, these tests should not be used for the same purpose. Clotting time-based assays should only be recommended as a screening test for the detection of FV mutations prior to confirmation by genetic testing. On the other hand, the ETP-based APC resistance assay, in addition to being able to detect any type of APCR, could be proposed as a global screening test as it assesses the entire coagulation process.
Keywords: activated protein C resistance; factor V Leiden; venous thromboembolism; blood coagulation tests; phenotype; thrombin generation; thrombophilia; hypercoagulable state